Relationship of adiponectin, leptin and reproductive endocrine hormones with insulin resistance in polycystic ovary syndrome patients with normal BMI - Weiwei Feng; Xianjing Xie; Yan Su; Rong Jin; Wei Shi (Gynecological Endocrinology)
Objective This study aimed to analyze the correlation of adiponectin (APN) and leptin (LEP), reproductive endocrine hormones with insulin resistance (IR) in polycystic ovary syndrome (PCOS) patients with normal body mass index (BMI).Methods Totally 160 PCOS patients were categorized into the Normal BMI (BMI: 18.5–25 kg/m2, n = 62) and High BMI (BMI > 25 kg/m2, n = 98) groups. Glucose indicators [fasting plasma glucose, fasting insulin and Homeostasis Model Assessment of Insulin Resistance (HOMA-IR)], lipid indicators [total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C)], adipokines [APN and LEP] and reproductive endocrine hormones [luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin (PRL), total testosterone (TT), dehy-droepiandrosterone sulfate (DHEAS) and estradiol (E2)] were collected, and their correlations were analyzed. The relationship of HOMA-IR with APN, LEP and reproductive endocrine hormones was subjected to multiple linear regression analysis.Results Correlation analysis revealed positive correlations of HOMA-IR with TC, TG, LDL-C, LEP, PRL, DHEAS and TT and negative correlations with HDL-C, APN, LH, FSH and E2 in PCOS patients with normal BMI. Multiple linear regression analysis showed that LH, FSH and E2 negatively affected HOMA-IR, while PRL positively affected HOMA-IR.Conclusion There were strong correlations of HOMA-IR in PCOS patients with normal BMI with APN, LEP, and reproductive endocrine hormones. Besides, LH, FSH, E2 and PRL expression had an important effect on IR in normal BMI PCOS patients, which provided a theoretical basis for the exploration of pathogenic mechanisms in normal BMI PCOS patients.